LEVEL OF CHROMOSOMAL ABERRATIONS, ACTIVE RIBOSOMAL GENES DOSE AND POLYMORPHISM OF DNA REPAIR GENES IN MINERS OF THE KEMEROVO REGION - Анна Александровна Тимофеева; Варвара Ивановна Минина; Ольга Александровна Соболева; Анастасия Владимировна Рыжкова; Яна Александровна Савченко; Марина Леонидовна Баканова; Татьяна Александровна Головина; Андрей Николаевич Глушков (Медицина в Кузбассе)
Objective. Study of the effects of production the environment factors on the miner genome, depending on the variants of the DNA repair genes XRCC2, XRCC3, and the individual dose active ribosomal genes clusters (AcRG).